Line Follower Robot Training and Introduction of Internet of Things (IoT) for Students in Jombang City - Eva Inaiyah Agustin; Riky Tri Yunardi; Winarno Winarno (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: During the Industrial Revolution 4.0, the Internet of Things (IoT) is the main pillar of people and machines connected to each other. It can be an intelligent system when combined with a robot. This is what underlies the importance of robotics and IoT training, especially to be introduced early on. Purpose: This activity aimed to improve students' knowledge and skills in technology. The target of this activity is high school students in Jombang City. Methods: It starts from the planning, implementation, and evaluation stages. Auditory, visual and kinesthetic techniques are used in this activity, which is in the form of interesting learning media such as power points, videos, as well as demonstrations and practices. Data collection techniques such as questionnaires, pre-test, and post-test, and running tests were carried out to measure the level of skills, knowledge, and satisfaction of participants. Results: A total of 85% of participants did not know about IOT and 83% of the participants already know what the robot. But only 17% ever make robots. Conclusion:  After this activity the participants' understanding increased by 20%. Their skills also increased as evidenced by the participants programming themselves so that the robot can run well on the track.